Up-regulation of miR-297 mediates aluminum oxide nanoparticle-induced lung inflammation through activation of Notch pathway. (April 2020) - Yun, Jun; Yang, Hongbao; Li, Xiaobo; Sun, Hao; Xu, Jie; Meng, Qingtao; Wu, Shenshen; Zhang, Xinwei; Yang, Xi; Li, Bin; Chen, Rui
Abstract: Exposure to Aluminum oxide nanoparticles (Al2 O3 NPs) has been associated with pulmonary inflammation in recent years; however, the underlying mechanism that causes adverse effects remains unclear. In the present study, we characterized microRNA (miRNA) expression profiling in human bronchial epithelial (HBE) cells exposed to Al2 O3 NPs by miRNA microarray. Among the differentially expressed miRNAs, miR-297, a homologous miRNA in Homo sapiens and Mus musculus, was significantly up-regulated following exposure to Al2 O3 NPs, compared with that in control. On combined bioinformatic analysis, proteomics analysis, and mRNA microarray, NF-κB-activating protein (NKAP) was found to be a target gene of miR-297 and it was significantly down-regulated in Al2 O3 NPs-exposed HBE cells and murine lungs, compared with that in control. Meanwhile, inflammatory cytokines, including IL-1β and TNF-α, were significantly increased in bronchoalveolar lavage fluid (BALF) from mice exposed to Al2 O3 NPs. Then we set up a mouse model with intranasal instillation of antagomiR-297 to further confirm that inhibition of miR-297 expression can rescue pulmonary inflammation via Notch pathway suppression. Collectively, our findings suggested that up-regulation of miR-297 expression was an upstream driver of Notch pathway activation, which might be the underlying mechanism involved in lung inflammation induced by exposure to Al2 O3 NPs. Graphical abstract: Image 1 Highlights: Up-regulation of miR-297 induced by Al2 O3 NPs suppressed expression level of NKAP. Suppression of NKAP triggered activation of Notch pathway in pulmonary inflammation. AntagomiR-297 can specifically target lung via intratracheal instillation. Inhibition of miR-297 in lung rescued pulmonary inflammation induced by Al2 O3 NPs. Abstract : Up-regulation of miR-297 mediates Al2 O3 NPs-induced lung inflammation through activation of Notch pathway.